Numerical investigation of turbulent forced convection flow in a two-dimensional curved surface cavity. Issue 1 (31st December 2022) - Sanga, Praveen J.; Kumar, Arbind; Mishra, Sabin K.
Abstract : A numerical study was carried out to investigate the thermal and flow fields of a two-dimensional vented cavity subjected to forced convection turbulent flow. The cavity with three distinct configurations of inlet and outlet ports having three different cases of top surfaces, i.e. flat, semi-elliptical and semi-circular was studied numerically for a range of Reynolds numbers. The objective of the study is to investigate the effect of the top curved wall surface on heat transfer in different configurations of inlet and outlet ports. The various results were presented for streamlines and thermal fields. The variations in the pressure-drop coefficient, local Nusselt number and average Nusselt number were also evaluated. The results show the significant dependence of heat exchange and pressure drop on Reynolds number, location of ports, and the height of the top curved wall surface. The rate of heat transfer was enhanced by increasing the height of the curved surface, but relatively high-pressure drop was observed in top curved surface cavity for the given Reynolds number. On the contrary, the semi-elliptical top surface cavity with inlet and outlet ports positioned on the same axis, displayed an improved performance in terms of maximum average Nusselt number and minimum pressure drop.